Short-Term Labor Supply Response to the Timing of Transfer Payments: Evidence from the SNAP Program - Mindy Marks; Silvia Prina; Redina Tahaj (Institute of Labor Economics (IZA), 2023)
We study the effect of the timing of SNAP payments on weekly labor supply using data from the CPS. We rely on exogenous variation in the fielding of CPS interviews relative to benefit receipt to estimate labor supply of SNAP eligible individuals at the end of their SNAP benefit cycle (i.e. about to receive benefits) compared to individuals at the start of their cycle (i.e. just received benefits). We find that the timing of SNAP benefits impacts labor supply at the intensive margin, while the extensive margin is unaffected. Conditional on being employed, eligible individuals at the end of their SNAP cycle are more likely to be absent from work compared to individuals at the start of their SNAP cycle. They are also less likely to temporarily shift to full time work. Results are more pronounced for individuals with higher predicted benefit amounts. Our findings suggest that a worsening of individuals' status (e.g. health problems, child care issues) at the end of their SNAP cycle adversely impacts short-term work presence.
Keywords: J22; I38; 330; consumption cycles; SNAP benefits; labor supply